Analisis Daya Dukung Ketersediaan Lahan Untuk Pembangunan Perumahan di Perkotaan (Studi Kasus : Ketersediaan Lahan di Kota Depok) - Zulkarnain Zulkarnain; Zefri Zefri; Jenniria Gukguk (Jurnal Kajian Wilayah dan Kota, 2022)
The carrying capacity of land availability for housing development in urban areas needs to be taken into account. So it is necessary to have an analysis that can calculate the carrying capacity of land availability for housing development that adjusts population growth in Depok City. The purpose of this research is to achieve land utilization for housing in accordance with spatial rules, with the objectives being land carrying capacity analysis to determine potential land, land capacity analysis and population analysis to determine land capacity for housing and population. The results of the research in sample locations that can represent the Depok City area show that the availability of potential land that can be developed for horizontal housing in 2038 has been greatly exceeded, meaning that there are a number of housing and a number of residents are not accommodated. And at present, based on the results of the site review, there are already several housing areas that are in locations that are not in accordance with spatial planning rules, these findings prove the hypothesis in this study.